2016
DOI: 10.1136/bmjopen-2015-010137
|View full text |Cite
|
Sign up to set email alerts
|

Association between subjective social status and cardiovascular disease and cardiovascular risk factors: a systematic review and meta-analysis

Abstract: ObjectiveTo determine the association between subjective social status (SSS), or the individual's perception of his or her position in the social hierarchy, and the odds of coronary artery disease (CAD), hypertension, diabetes, obesity and dyslipidaemia.Study DesignSystematic review and meta-analysis.MethodsWe searched PubMed, MEDLINE, EMBASE, CINAHL, PsycINFO, SocINDEX, Web of Science and reference lists of all included studies up to October 2014, with a verification search in July 2015. Inclusion criteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 42 publications
8
110
1
6
Order By: Relevance
“…First, socioeconomic position is a complex construct and a variety of indicators may be utilized, like income, wealth, occupation and other individual and contextual markers and indexes [4244]. Our analyses were based exclusively on the level of education, with several intrinsic limitations, such as the differential economic and social returns across gender and race strata, over time and geopolitical context, and the lack of information about the quality of education.…”
Section: Discussionmentioning
confidence: 99%
“…First, socioeconomic position is a complex construct and a variety of indicators may be utilized, like income, wealth, occupation and other individual and contextual markers and indexes [4244]. Our analyses were based exclusively on the level of education, with several intrinsic limitations, such as the differential economic and social returns across gender and race strata, over time and geopolitical context, and the lack of information about the quality of education.…”
Section: Discussionmentioning
confidence: 99%
“…According to a prospective cohort study, SSS is a strong predictor of ill health, irrespective of education, occupation and income (15). Lower SSS is also associated with increased risk of hypertension, dyslipidemia, coronary artery disease, diabetes and obesity (16, 18). Such associations between SSS and health outcomes may be due to the effects of perceived social status on the underlying physiology of feeding behavior, which may impact body size and body fatness (12, 1922).…”
Section: Introductionmentioning
confidence: 99%
“…This subjective social standing or class is largely based on perceived relative possession of material and social resources (wealth, education, occupational prestige) compared with others, given the role of such resources in signifying and reifying status. Cross-sectional investigations and metaanalysis on the relationship between subjective socioeconomic status and health outcomes have suggested that individuals who report lower levels of subjective socioeconomic status and rank are more likely to be at risk for weight gain, adiposity, diabetes, and overweight/obesity even when controlling for objective indicators of socioeconomic status (11)(12)(13)(14). One pilot feasibility study using a small sample has implied that people placed into disadvantaged social roles subsequently consume more calories, but under circumstances where those in disadvantaged roles are exposed to greater stress and potential aggression from those in dominant roles (15).…”
mentioning
confidence: 99%